Natural killer cytolytic activity is associated with the expression of killer cell immunoglobulin-like receptors on peripheral lymphocytes in human - Toshiaki Kogure; Naoki Mantani; Shinya Sakai; Yutaka Shimada; Jun'ichi Tamura; Katsutoshi Terasawa (Mediators of Inflammation)
Although it has been shown that killer cell immunoglobulin-like receptors (KIRs) on peripheral lymphocytes are upregulated by interleukin-2 (IL-2), which activates natural killer (NK) activity, it has not been demonstrated whether the expression of KIRs is related to NK activity. Therefore, we investigated the association between the KIR expression on lymphocytes and NK activity. CD158a/b expression on lymphocytes obtained from 37 subjects was analyzed using flow cytometry. Simultaneously, NK activity was measured each sample using a 51Cr-release assay. Additionally, lymphocytes were cultured in RPMI 1640 medium with or without IL-2 for 48 h, and then their CD158a/b expression and NK activity was analyzed. CD158a/b expression was significantly correlated with NK activity. Especially, the percentage of CD16+CD158a+ and CD8+CD158a/b+ cells in lymphocytes showed a highly significant correlation with NK activity. However, analysis of CD8+ and CD16+ cells revealed that there was only a significant correlation between the percentage of CD8+CD158a+ cells among only CD8+ cells and NK activity. The upregulation of CD16+CD158a+/b+ cells in response to IL-2 tended to be related to the increase of NK activity, but the relationship was not significant. In conclusion, the level of KIR expression was correlated with NK activity, and IL-2 treatment resulted in an increase of NK activity as well as KIR expression, suggesting that upregulation of KIRs enhances the ability to sort target cells, such as virus-infected cells from uninfected cells, according to major histocompatibility complex class I expression.